The effects of financial development towards economic growth / Emilya Nur Amri - Amri, Emilya Nur (2017)
Economic growth can be considered among the most critical indicators in a country which is revealed in many literatures or past studies. Thus, this research is done to identify the factors that affect economic growth. That being the case, the matter in the study is in regards to financial development and its effects towards economic growth. Hence, the main purpose is to examine whether financial development does influence the economic growth in Malaysia, where suitable factors for financial development are being determined and chosen from the prior researches. Hence, this study is carried out by using time series data in the context of Malaysia. The multiple linear regression model is regressed using the Ordinary Least Square (OLS) for over 30 years of data analysis. The sample data is collected from 1895 to 2014. The data to this study is obtained from the source of World Bank Databank. The result is analysed through the software of Eviews 8, including descriptive analysis, correlation analysis, multiple regression analysis and tests on assumptions. Throughout this study, each independent variable, which includes domestic credit to private sector, liquid liabilities, and stocks traded, except for market capitalization, are resulted as positively significant variables in determining the economic growth in Malaysia.